2012
DOI: 10.1111/j.1365-3024.2012.01362.x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of regulatory dendritic cells in inflammatory responses during Trypanosoma evansi infection

Abstract: Summary Trypanosoma evansi (T. evansi) causes a wasting disease in almost all mammals. Trypanosoma evansi infection gives rise to the inflammatory responses that contribute to the development of inflammation‐associated tissue injury. To determine what kinds of inflammatory molecules play roles in the pathogenicity of T. evansi infection, polymerase chain reaction array analysis was performed on samples from the infected and uninfected mice. The inflammatory cytokine and chemokine storm, caused mainly by macrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 62 publications
(74 reference statements)
0
9
0
Order By: Relevance
“…Behind the inflammatory cytokine and chemokine storm caused mainly by macrophages in T. evansi infections, increased expression levels for Ccl8 and Il10 in splenocytes suggested an increase in the number and activity of regulatory dendritic cells (DCs). The regulatory DCs became prevalent during the progress of infection, therefore reducing the amount of inflammatory DCs, and as a potential regulator of the inflammatory responses, suggesting the use of the inflammatory responses to immunosuppress the host, but regulation to avoid irreversible pathophysiological effects [182]. …”
Section: Immunosuppressive Effectsmentioning
confidence: 99%
“…Behind the inflammatory cytokine and chemokine storm caused mainly by macrophages in T. evansi infections, increased expression levels for Ccl8 and Il10 in splenocytes suggested an increase in the number and activity of regulatory dendritic cells (DCs). The regulatory DCs became prevalent during the progress of infection, therefore reducing the amount of inflammatory DCs, and as a potential regulator of the inflammatory responses, suggesting the use of the inflammatory responses to immunosuppress the host, but regulation to avoid irreversible pathophysiological effects [182]. …”
Section: Immunosuppressive Effectsmentioning
confidence: 99%
“…Mice infected with T. evansi strain L2 showed a strong up-regulation of IL-10 and CCL8 which were responsible for the expansion of regulatory dendritic cells (DCs) during the acute phase of parasite infection (Mekata et al 2012). Inoculation of mice with regulatory DCs significantly prolonged their survival rate after infection when compared with untreated controls (Mekata et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The role of non-inflammatory IL-10 mediated responses during T. evansi infections has been studied in mice and cattle (Mekata et al 2012(Mekata et al , 2015. Mice infected with T. evansi strain L2 showed a strong up-regulation of IL-10 and CCL8 which were responsible for the expansion of regulatory dendritic cells (DCs) during the acute phase of parasite infection (Mekata et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The cellular and molecular components that govern this delicate balance are necessary to understand the pathology of T. evansi infection. We have previously reported that regulatory dendritic cells (DCs), which secret a high dose of IL-10 and activate regulatory T cells [ 19 , 22 ], were induced in mice experimentally infected with T. evansi and controlled excessive inflammation [ 11 ]. In this study, we reveal that the phenomenon also occurs in cattle, the natural hosts of T. evansi .…”
mentioning
confidence: 99%
“…[ 4 ]. Extraction of total RNA from the peripheral blood mononuclear cells (PBMCs) and quantification of the cytokines by real-time PCR were performed as described by Mekata et al [ 11 ]. We set the mean cytokine expression of one day and just before the injection of trypanosome as the reference of relative ratio.…”
mentioning
confidence: 99%